Problems of Voting Rights in Elections in Siak Regency, Riau Province - Sahat Matua; Adrian Faridhi; Sudi Fahmi; Alexander Yandra (JOELS: Journal of Election and Leadership, 2020)
Elections are a means of democracy used to rotate governmental circles, both executive and legislative powers. Voter participation in the holding of elections in 2019 is very high compared to the previous elections and therefore the potential for voters who cannot use their voting rights is very high as well. The research method used is sociological juridical research methods, with data collection techniques from primary data sources, data collection techniques by interviewing, observing, and studying literature. Problems in the form of the exercise of voting rights in Siak Regency in the General Election, that every voter can use their voting rights at the polling station, but in the implementation of simultaneous elections in 2019 in Siak District there are still Voters who cannot give their voting rights due to the endless availability of ballots, this is due to lack of effective in carrying out the data collection of potential voters conducted by election organizers when updating data, systems and infrastructure and the readiness of organizers to face simultaneous elections, low public awareness of their own voting rights.